The effect of good corporate governance on the financial performance of property and real estate sub-sector companies listed on the Indonesia Stock Exchange - Fuad Alamsyah, Muhammad; Yulianti, Yulianti (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2022)
Good Corporate Government (GCG) is a process and a structure applied in operating a company, intending to improve the company management following the principles of GCG, namely transparency, accountability, responsibility, independence, fairness, and equality. GCG affects the improvement of the company's financial performance. This study aims to find the effect of independent commissioners, managerial ownership, institutional ownership on the financial performance of the property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. This study uses an associative research method with a quantitative approach. The sampling technique used is purposive sampling with several criteria. It has a sample of 40 companies obtained from an initial population of 48 companies and analyzed using multiple linear regression with SPSS 21. The results of this study indicate that partially, the independent board of directors, managerial ownership, and institutional ownership have no significant effect on financial performance. Simultaneously based on F-test, the variables consisting of the independent board of commissioners, managerial ownership, and institutional ownership have a significant effect on profitability.